The Effectiveness of Alum Made of Uncoated Aluminium Foil Waste in Improving the Quality of Liquid Waste of the Tofu Industry - Nyoman Sri Widari; Agung Rasmito; Abas Sato (Jurnal IPTEK, 2021)
Aluminium foil waste increases every year in line with technology development, especially in the food and beverage industry. It will cause significant environmental problems because the packaging cannot be destroyed in the soil. Therefore, it is necessary to reprocess a large amount of aluminium waste into an alternative product such as alum which can be applied directly to the treatment of liquid tofu waste. In this study, uncoated aluminium foil waste was used, which was taken at random landfill sites and then washed and cut into small pieces. Dissolution of aluminium using KOH solution then the solution obtained is reacted with H2SO4 solution and the reaction is carried out at a temperature of 70oC. The experimental results got a maximum yield of 63.69% with Al2O3  content of 15.18% using 3 M KOH concentration and 5 M H2SO4 concentration. The obtained alum was then applied to the tofu industrial liquid waste. With the use of 800 ppm alum, there was a 60% decrease in the colour content of the Pt-Co unit, a 95.8% decrease in NTU and a 63.33% decrease in TDS. The quality of the liquid waste obtained met the technical requirements of raw water that can be treated by SNI 6773: 2008.